EKONOMI SYARIAH SEBAGAI MODEL PEMBANGUNAN BERKELANJUTAN DALAM PERKEMBANGAN PEMIKIRAN SISTEM EKONOMI: PERSPEKTIF HISTORIS TANTANGAN KONTEMPORER - Evi Fortuna Sukiran Putri; Fauzatul Laily Nisa (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Abstract. This article explains the history of Islamic economic thought from the classical era to the resurgence era. The classical era of Islamic economics began during the reign of the Prophet Muhammad SAW as the beginning of the development of Islamic economics which was continued by the reign of Khulafa’ urrasyidin and continued to develop until the contemporary era. Sharia eco nomics is based on Islamic Aqidah which is based on the legal sources of the Koran and hadith. Sharia economics focuses on the benefit and fair distribution of assets, as well as safeguarding the wealth of Muslims. There are various policies taken from each era to maintain justice and prosperity of society in the sharia economic system. Not a few Muslim scholars have mobilized their thoughts to continue to perfect Islamic economics from time to time. Keywords: Sharia Economics; History; Contemporary. Abstrak. Artikel ini menjelaskan mengenai Sejarah pemikiran ekonomi islam dari era klasik hingga era resurgensi. Era klasik ekonomi islam dimulai dari masa pemerintahan Rasulullah Muhammad SAW sebagai awal berkembangnya ekonomi islam yang dilanjutkan oleh masa pemerintahan khulafa’urrasyidin dan terus berkembang hingga masa kontemporer. Ekonomi syariah berbasis pada Aqidah islamiah yang didasarkan oleh sumber hukum Al-Qur’an dan hadist. Ekonomi syariah berfokus pada kemaslahatan dan keadilan distribusi harta, serta menjaga kekayaan umat muslim. Terdapat berbagai kebijakan yang diambil dari masing-masing era guna menjaga keadilan dan mensejahterakan Masyarakat dalam system ekonomi syariah. Tidak sedikit cendekiawan muslim yang mengerahkan pemikiran-pemikirannya untuk terus menyempurnakan ilmu ekonomi islam dari masa kemasa. Kata kunci: Ekonomi Syariah; Sejarah; Kontemporer.